Developing Innovation and Based on Smart Madrasah Model in Malang City - Juniarni, Cittra; Ali, Nur (Idarah (Jurnal Pendidikan dan Kependidikan), 2022)
Concept of smart madrasah is created as a response on complexity of challenges in education world. This research aims to determine the model of smart madrasah in Malang city. The development model is determined by measuring madrasah readiness level for information and communication technology. This research is mix method using consequential explanatory strategy through quantitative stage in data collection technique and then the data analysis is followed by qualitative in interpretation stages of overall analysis. Research location is Al Izzah senior high school Batu having high potential in implementing Smart Madrasah. Results of the research show that the madrasah has e-readiness on ICT by 94.1 %, e-literacy level on ICT by 99.4 %.